Fully Homomorphic Encryption: Revolutionizing Payment Security - Hirenkumar Patel, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
with legacy systems, performance overhead, standardization requirements, and interoperability concerns across heterogeneous payment ecosystems. This article analyzes these challenges alongside emerging optimization techniques and implementation strategies that show promise for overcoming current adoption barriers. As computational efficiency continues to improve through hardware acceleration and algorithmic innovations, FHE stands poised to revolutionize payment security by fundamentally altering how sensitive financial data is processed in distributed environments.
Keywords: Homomorphic Encryption; Payment Security; Tokenization, Card-Not-Present Fraud; Privacy-Preserving Computation